# Write the following equation in the general form ax + by + c = 0 for the equation 2x + y = 6.

We will use the concept of linear equations in order to find the required answer.

## Answer: General form ax + by + c = 0 for the equation 2x + y = 6 is equal to 2x + y - 6 = 0.

Let us see how we will use the concept of linear equations in order to find the required answer.

**Explanation:**

The general form of a linear equation in two variables is given by ax + by + c = 0

We have been given the equation 2x + y = 6 which has to be converted to general form.

On transposing 6 on the left hand side we will get our linear equation 2x + y = 6 in general form and it will be equal to 2x + y - 6 = 0.

In general form a = 2, b = 1, c = -6 for the equation 2x + y - 6 = 0.